S100A8 in Serum, Urine, and Saliva as a Potential Biomarker for Systemic Lupus Erythematosus - Kim, Ji-Won; Jung, Ju-Yang; Lee, Sang-Won; Baek, Wook-Young; Kim, Hyoun-Ah; Suh, Chang-Hee (Frontiers in Immunology, 2022)
Objectives This study aimed to elucidate the potential of serum, urine, and saliva S100 calcium-binding protein A8 protein (S100A8) levels as biomarkers for systemic lupus erythematosus (SLE). Methods Serum, urine, and saliva samples were obtained from 249 patients with SLE from the Ajou lupus cohort and 52 age-and sex-matched healthy controls (HCs). The concentrations of S100A8 were quantified using an enzyme-linked immunosorbent assay, and a receiver operating characteristic curve was used to analyze whether they may be used as biomarkers for diagnosing SLE. Results Among 249 SLE patients included in our study, the mean SLE disease activity index (SLEDAI)-2K was 7.16 ± 5.61, and the number of patients with lupus flare was 11. Patients with SLE showed a 2.7-fold increase in serum S100A8 levels compared with that in HCs (1,890.6 pg/ml vs. 709 pg/ml, p < 0.001). In urine and saliva, the average S100A8 levels were significantly higher in patients with SLE compared with those in HCs (urine, 2,029.4 pg/ml vs. 1,096.7 pg/ml, p = 0.001; saliva, 290,496.3 pg/ml vs. 47,742 pg/ml, p < 0.001). For SLE diagnosis, the area under the receiver operating characteristic curve was 0.831 for serum S100A8 (95% confidence interval [CI], 0.765–0.897), 0.751 for urine S100A8 (95% CI, 0.648–0.854), and 0.729 for salivary S100A8 (95% CI, 0.646–0.812). Pearson’s correlation analysis showed that S100A8 in serum, urine, and saliva was significantly associated with the SLEDAI (r = 0.267, p < 0.001; r = 0.274, p < 0.001; r = 0.629, p < 0.001, respectively). Among the clinical manifestations, nephritis was the most influential factor related to SLE in the concentration of S100A8 in serum, urine, and saliva. Conclusion This is the first study to show that the expression of S100A8 in serum, urine, and saliva is significantly higher in patients with SLE than in HCs and is associated with disease activity markers. Therefore, we suggest that S100A8 protein could be a potential biomarker for SLE.